A retrospective study of the epidemiology and histological subtypes of ovarian epithelial neoplasms at Charlotte Maxeke Johannesburg Academic Hospital. Issue 1 (3rd December 2021) - Pillay, Lusela; Wadee, Reubina
Abstract : Background: Epithelial ovarian neoplasms constitute the majority of ovarian tumours and are the most common malignant ovarian neoplasm. They are the eighth leading cause of cancer deaths worldwide. This study evaluated the epidemiology and histological subtypes of epithelial ovarian neoplasms at a single institution. Methods: This retrospective, quantitative analysis evaluated 123 epithelial ovarian neoplasms between 2013 and 2017 and classified them according to age, biological behaviour and histological subtype. Results: Of 123 cases, 64 (52.0%), tumours were benign, 30 (24.4%) were borderline and 29 (23.6%) tumours were malignant. Serous cystadenoma was the most common benign tumour (42.2%). Mucinous borderline tumours were the most common borderline neoplasm (50.0%). High-grade serous carcinoma was the most common carcinoma (58.6%). Patients presented at an older age with borderline tumours and malignant tumours, compared with patients with benign tumours. Conclusion: The current study demonstrated that serous tumours were the most common type of benign and malignant tumours whilst mucinous neoplasms were the commonest subtype of borderline tumours. These findings are congruent with multiple similar studies. A higher number of borderline tumours were seen in this cohort in comparison with previous studies. This suggests a need for additional sampling of borderline tumours, over and above the international standard, in our population, to definitively exclude invasive malignancy. This study also demonstrated the histological progression of benign serous and mucinous tumours to borderline tumours and low-grade serous carcinoma and mucinous carcinoma, respectively, which supports the stepwise tumour progression model of these tumours.